Developing assessment rating tool on authenticity in adaptive reuse of heritage building in Malaysia / Hasni Suryani Mat Hasan - Mat Hasan, Hasni Suryani (2021)
Heritage building consists of past generation history, memory, and culture. In order to protect heritage building, it is necessary to adapt it to new functions by modifying the functionality of heritage building to support the next generation's need while at the same time retaining its authenticity. However, the stakeholders' eagerness with respect to this conservation method, has led to the loss of heritage building authenticity. From intensive reading, surprisingly, it is found that in local authority conservation guidelines are still lacking and there is no satisfactory method to control the authenticity in the adaptive reuse of heritage building. This is disturbing, although authenticity is a prime concern in conservation. Hence, the aim of the study is to develop assessment rating tool on authenticity in the adaptive reuse of heritage buildings in Malaysia based on authenticity in conservation. To achieve the research aim, three research objectives were established which includes to establish the main building elements listed for assessment of authenticity in the adaptive reuse of heritage building, to identify the key indicators of authenticity in adaptive reuse for the main building elements in a heritage building and to develop assessment rating tool on authenticity in adaptive reuse of heritage building in Malaysia based on the authenticity in conservation. To achieve the research objectives, multiple sources of data were applied in a case study that consisted of semi structured interview with experts, observation in adaptive reuse of heritage building and document analysis on four guidelines. The findings from this study shows that the study has generated 20 main building elements listed for assessment of authenticity in adaptive reuse of heritage building and established the 15 key indicators of authenticity in adaptive reuse for the main building elements in heritage building. This was later integrated in the development of assessment rating tool. The assessment rating tool developed provides the guidance needed to rate the value of authenticity retained before, during and after adaptive reuse work. The output will give insight into the level of successful authenticity controlled in adaptive reuse of heritage building, and can be used to support current conservation guidelines, and fill the loophole in current practice assessment in adaptive reuse of heritage building work. Therefore, the authenticity of heritage building in adaptive reuse work can be controlled, the intervention can be minimized and the authenticity issue in adaptive reuse can be solved.